Propuesta didáctica para el desarrollo psicomotor de estudiantes de 5 años del nivel inicial - Barrueto Jara, Anahí Mitzu Selmith (2023)
The present basic research titled: Didactic proposal for the psychomotor development of 5- year-old students of the initial level, had as objective to elaborate the proposal of didactic games "Caritas Felices" for the psychomotor development of 5-year-old students. The type of research was basic with a purposeful descriptive design, with a population of 36 children from section "A" and "B" of the C.E.E. Rafael Narváez Cadenillas and with a sample of 18 children from the 5-year-old classroom "A" of the aforementioned Garden. Observation was used as a technique and a checklist was used as an instrument. The proposal "happy faces" didactic games program was elaborated, which is based on a series of activities with playful games for 5-year-old students, it has two dimensions, the adequate psychomotor material and the good performance of the teacher, likewise, The checklist was elaborated with the purpose of evaluating the psychomotor development of the children, validated and reliable. The results show that the level of psychomotor development of the 5-year-old students of the C.E.E. Rafael Narváez Cadenillas is at a medium level in 61%, low in 28% and high in 11%, so it is necessary to implement a proposal that helps in the psychomotor development of children.